"Polluting our kids' imagination"? Exploring the power of Lego in the discourse on sustainable mobility. Issue 1 (10th December 2020) - Stockmann, Nils; Graf, Antonia
Abstract: This article explores the picture of sustainable mobility drawn by the world's biggest toy company, Lego, and how this picture is potentially received and consolidated by Lego players. The company has already attracted the attention of scholars and activists alike regarding their influence on attitudes toward gender and race. The question of their influence on sustainable development, however, has not yet been tackled, amidst the overdue socio-cultural transformation of sectors such as mobility. We combine research on discursive business power from the field of international political economy with insights into the rituals of play from social psychology as well as science and technology studies. The heuristic device of the re-signification process of discursive power aligns these perspectives and generates sub-questions for the empirical investigation. As outlined in our methodology section, we deliver a qualitative-hermeneutic analysis of Lego building sets and commercials. In the results section we show, that playing with Lego products encourages children to re-signify the norms of unsustainable mobility, especially the dominance of the car. In the discussion and conclusion of our contribution we argue that the normalization of car-centered built environments and associated lifestyles, as well as omnipresent fossil-fuel dependency, hinder Lego's potential to deliver transformative stimuli that promote a more sustainable mobility sector.